The Woman Question in Medicine: An Update - Lindemann, Hilde (The Hastings Center report, 2012)
The Women's Movement has greatly benefitted women in the workplace. What about in their encounters with medicine? This paper reviews the history of physicians’ attitudes toward women and then considers three contemporary areas of medicine in particular: health research relevant to women, health policies, and women's success at working their way into the medical profession. The picture that emerges is somewhat less than rosy. The androcentrism that has been so glaring in the history of medicine has not entirely gone away. Women and their concerns are still considered less important than men's, and women are valued more for what they provide than for who they are themselves. These problems are mostly not the fault of specific physicians or other individuals; they are, rather, systemic problems—the result of social practices and institutions that work together quite impersonally to favor the interests of men over women. Correcting them requires listening to women's voices better than medicine, or bioethics, has so far managed to do.